2018
DOI: 10.1097/md.0000000000012792
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors of residual lesions and recurrence of the high-grade cervical intraepithelial lesions (HSIL) patients with positive-margin after conization

Abstract: The aim of this study was to illuminate risks factors of residual lesions, and recurrence of the high-grade cervical intraepithelial lesions (HSIL) patients with positive margin who underwent cervical conization.A retrospective cohort study of 218 patients with positive margin after conization, including cold knife conization (CKC) and loop electrosurgical excisional procedure (LEEP), and follow-up from 2013 through 2016. The diagnosis of residual disease and recurrence were established and confirmed by biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 18 publications
12
46
0
1
Order By: Relevance
“…In this study, the proportion of premenopausal cases of CIN was signi cantly higher than that of SCC cases, and logistic analysis found that premenopause was one of the independent risk factors for the progression of CIN. Chen et al [18] studied patients with CIN who relapsed after receiving cervical conization or LEEP treatment, and the reoccurrence rate of premenopausal patients was signi cantly higher than that of menopausal patients, which is consistent with this study. However, Renata B et al [19] reported that postmenopausal CIN patients were more prone to interstitial in ltration and progression to invasive cervical cancer.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the proportion of premenopausal cases of CIN was signi cantly higher than that of SCC cases, and logistic analysis found that premenopause was one of the independent risk factors for the progression of CIN. Chen et al [18] studied patients with CIN who relapsed after receiving cervical conization or LEEP treatment, and the reoccurrence rate of premenopausal patients was signi cantly higher than that of menopausal patients, which is consistent with this study. However, Renata B et al [19] reported that postmenopausal CIN patients were more prone to interstitial in ltration and progression to invasive cervical cancer.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the proportion of premenopausal cases of CIN was significantly higher than that of SCC cases, and logistic analysis found that premenopause was one of the independent risk factors for the progression of CIN. Chen et al [18] studied patients with CIN who relapsed after receiving cervical conization or LEEP treatment, and the reoccurrence rate of premenopausal patients was significantly higher than that of menopausal patients, which is consistent with this study. However, Renata B et al [19] reported that postmenopausal CIN patients were more prone to interstitial infiltration and progression to invasive cervical cancer.…”
Section: Clinical Factors Related To the Occurrence And Progression Osupporting
confidence: 89%
“…Preinvasive cervical lesion is limited to epithelial and if left untreated, may progress to advanced form of cervical cancer (Garcia et al, 2012). The incidence of cervical cancer as one of the most common gynecological cancers has been increasing in recent decades and cervical intra-epithelial neoplasia (CIN) is known as one of the precursors to cervical cancer (Chen et al, 2018). Generally, CIN is divided into (i) CIN I which is equivalent to mild dysplasia, (ii) CIN II which is equivalent to moderate dysplasia, and (iii) CIN III which is equivalent to severe dysplasia or in-situ carcinoma (Rock and Jones, 2016).…”
Section: Introductionmentioning
confidence: 99%